Fiskální decentralizace v České republice - Sedláková, Lucie (Univerzita Pardubice, 2006)
V obecné části bakalářské práce jsou vymezeny pojmy fiskální federalismus, fiskální decentralizace, daně a dotace rozpočtu. Ve speciální části se zabývám druhy redistribucí na jednotlivých úrovních územní správy.

In the common part are described the terms of the fiscal federalism, the fiscal decentralization, the taxes and the budget grants. In the special part is focus taken on the types of redistributions on the individual levels of territorial administration.
Fiscal decentralization in the Czech Republic
Keywords: federalism; decentralizations; redistributions; Taxes; grants; federalismus; decentralizace; redistribuce; Daně; Dotace